Determination of surface activity of crude extracts from various plants - Hadi, J. N.; Bakhtiar, M. Taher; Ahmad, Kausar (2008)

(untitled)
Natural rubber latex and various milks produced by mammals are stabilised by proteins, and are examples of natural colloidal systems. In fact, milk casein has been for a long while isolated, to be later incorporated in manufactured products. Numerous work involving natural substances in pharmaceuticals, cosmetics and toiletries have been reported and many of these were later commercialized. However, the specific uses of these natural products as surfactants have not been established. In order to find out suitable source of potential surfactants for the preparation of pharmaceutical emulsions or suspensions, the ethanol/water crude extracts from eleven plants were used in this study. Incidentally, these plants have been used in various forms for medicinal purposes. The surface activities of these crude extracts were determined by measuring the surface tension of water containing various concentrations of extracts using the Du Nouy ring method. Measurements were carried out at 25C. Typical decrease in the surface tension of water as would be observed in the presence of surfactants was observed. However, the decrease due to the addition of Trigonella foenum (fenugreek) and Andrographis paniculata (hempedu bumi) was more significant than others with the surface tension lowered to 34.5 and 33.3 mN/m respectively. Presence of lecithin in the crude extract of T. foenum may be responsible for the high surface activity. The inclusion of T. foenum in various commercially available medicinal and personal care formulations is common in South Asia. However, the limited use of A. paniculata, a Malaysian indigenous species, is confined to traditional medicine only. The least surface active crude extracts were those from Fagraea obovata (tengkok biawak) and Eurycoma longifolia (tongkat ali). The critical micelle concentrations (CMC) of the crude extracts were obtained from a plot of surface tension against the log concentration of the crude extracts. The results showed that T. foenum has the lowest CMC at 0.017 % w/v.